Dynamic response of offshore wind turbine supported by suction bucket in clay considering scour - Cheng, Xinglei; Fang, Ziwen; Li, Qiang; El Naggar, M. Hesham; Lu, Dechun; Du, Xiuli (Ocean engineering, 2024)
The suction bucket foundation offers cost-effective and simple construction method for offshore wind turbines (OWTs). However, marine environment involves complex loading schemes, where suction bucket-supported OWTs would be subjected to wind, waves, currents, and earthquake loading, and may be subject to scour caused by prolonged wave and current actions. Currently, there is a paucity of research on how scour influences the dynamic response of suction bucket-supported OWTs. This study systematically investigates the influence of scour on the dynamic responses of suction bucket-supported OWTs under seismic, wind, and wave loads through comprehensive three-dimensional numerical analysis. Research findings demonstrate that scouring can decrease the natural frequency of suction bucket-supported OWTs by up to approximately 1% and the lateral ultimate bearing capacity by up to approximately 10%. Scouring amplifies the dynamic response of OWTs under wind-wave loads, with the wind speed exerting a more pronounced influence compared to the wave height. Scouring weakens the bucket-soil kinematic interaction and increases energy dissipation, which reduces the seismic response of the wind turbine structure. Seismic loads predominantly influence tower vibrations compared to wind-wave loads. In scenarios where earthquakes coincide with wind waves, wind-wave loads can mitigate the acceleration induced by seismic forces to some extent. There exists a nonlinear coupling relationship between wind and wave loads, as well as earthquake loads, making it advisable to employ a fully coupled method for OWTs response calculations. •A numerical method is developed for analyzing dynamic responses of suction bucket OWT in clay considering scour.•The influence of scouring on the natural frequency and ultimate bearing capacity of suction bucket OWT is investigated.•The influence of scouring on dynamic response of suction bucket OWT under wind-wave-seismic loads is investigated.